Clinical Application of Circulating Tumor Cells and Circulating Endothelial Cells in Predicting Bladder Cancer Prognosis and Neoadjuvant Chemosensitivity - Yang, Xiao; Lv, Jiancheng; Zhou, Zijian; Feng, Dexiang; Zhou, Rui; Yuan, Baorui; Wu, Qikai; Yu, Hao; Han, Jie; Cao, Qiang; Gu, Min; Li, Pengchao; et al. (Frontiers in Oncology, 2022)
Purpose To investigate the role of circulating rare cells (CRCs), namely, circulating tumor cells (CTCs) and circulating endothelial cells (CECs), in aiding early intervention, treatment decision, and prognostication in bladder cancer. Methods A total of 196 patients with pathologically confirmed bladder cancer, namely, 141 non-muscle invasive bladder cancer (NMIBC) and 55 muscle invasive bladder cancer (MIBC) patients. There were 32 patients who received cisplatin-based neoadjuvant chemotherapy (NAC) followed by radical cystectomy (RC). Subtraction enrichment combined with immunostaining-fluorescence in situ hybridization (SE-iFISH) strategy was used for CTC/CEC detection. Kaplan–Meier analysis and Cox regression were used to evaluate the overall survival (OS) and recurrence-free survival (RFS). Receiver operator characteristic analysis was used to discriminate NAC sensitivity. Results CTCs and CECs were related to clinicopathological characteristics. Triploid CTCs, tetraploid CTCs, and total CECs were found to be higher in incipient patients than in relapse patients (P = 0.036, P = 0.019, and P = 0.025, respectively). The number of total CECs and large cell CECs was also associated with advanced tumor stage (P = 0.028 and P = 0.033) and grade (P = 0.028 and P = 0.041). Remarkably, tumor-biomarker-positive CTCs were associated with worse OS and RFS (P = 0.026 and P = 0.038) in NMIBC patients underwent TURBT. CECs cluster was an independent predictor of recurrence in non-high-risk NMIBC patients underwent TURBT (HR = 9.21, P = 0.040). For NAC analysis, pre-NAC tetraploid CTCs and small cell CTCs demonstrated the capability in discriminating NAC-sensitive from insensitive patients. Additionally, tetraploid CTCs and single CTCs elevated post-NAC would indicate chemoresistance. Conclusion CTCs and CECs may putatively guide in diagnosis, prognosis prediction, and therapeutic decision-making for bladder cancer.